1998
DOI: 10.1016/s0022-2275(20)32526-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that microsomal triglyceride transfer protein is limiting in the production of apolipoprotein B-containing lipoproteins in hepatic cells

Abstract: The microsomal triglyceride transfer protein (MTP) is a heterodimeric lipid transfer protein that is required for the assembly and secretion of apolipoprotein B (apoB)-containing lipoproteins. A key unresolved question is whether the MTP-mediated step is rate limiting. To address this, a unique experimental strategy was used that allowed the in situ modulation and measurement of MTP triglyceride transfer activity. In order to accomplish this, an irreversible photoaffinity inhibitor, BMS-192951, was designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 31 publications
(31 reference statements)
2
19
0
Order By: Relevance
“…This finding is particularly interesting as our experimental model was the wild-type C57BL/6 mouse on normal chow without addition of lipid to the diet. Our results suggest that MTP is rate-limiting for hepatic VLDL secretion, as recently suggested by Jamil et al (29) and Liao, Kobayashi, and Chan (30) based on in vitro studies. In vitro studies using pharmacological MTP inhibitors have established that decreased MTP activity results in a decrease of TG and apoB secretion (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is particularly interesting as our experimental model was the wild-type C57BL/6 mouse on normal chow without addition of lipid to the diet. Our results suggest that MTP is rate-limiting for hepatic VLDL secretion, as recently suggested by Jamil et al (29) and Liao, Kobayashi, and Chan (30) based on in vitro studies. In vitro studies using pharmacological MTP inhibitors have established that decreased MTP activity results in a decrease of TG and apoB secretion (23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 89%
“…However, the question of whether increased MTP activity over basal levels of expression results in increased VLDL and apoB secretion in vivo has not yet been answered. Interestingly, a recent in vitro study suggested that MTP might be limiting for the secretion of apoB-containing lipoproteins (29). The same study reported that attempts to increase MTP activity by transfecting hepatoma cell lines with an expression plasmid encoding MTP were unsuccessful (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are several types of data on cells and animals suggesting that MTP is rate limiting for production of lipoproteins. Using a photo-affinity inhibitor in rat hepatoma cells, Jamil et al (7) indicated that the MTP-mediated lipid transfer step was the rate-limiting step in the production of apoB-containing lipoproteins. By using an MTP inhibitor, Wetterau et al (33) showed that apoB-containing lipoproteins within the plasma of experimental animals were decreased proportionally with druginduced MTP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…5A , lanes 2 and 4). This quantitative difference in secretion of apoB-41F from C127 cells in the presence or absence of cotransfected MTP suggests that, although MTP may be present in these cells, it is limiting (31).…”
Section: Density Gradient Analysis Of Apob-41f Secreted From C127 Cellsmentioning
confidence: 96%